The Effect Of Additives On The Properties Of Oil Palm Trunk Binderless Particleboard - Lamaming, Junidah (2012)
In this study, the effects of additives on the properties of oil palm trunk binderless board were evaluated through a series of mechanical, physical and chemical analyses. Ten types of binderless boards from oil palm trunk particles were made that include control boards, boards with addition of additives namely xylose, sucrose, glucose and potato starch, boards made from oil palm trunk particles that were extracted with hot water, and boards made from oil palm trunk particles that were extracted with hot water with addition of additives.